2014
DOI: 10.5901/mjss.2014.v5n23p372
|View full text |Cite
|
Sign up to set email alerts
|

Local Community Participation in the Conservation of the Naga Fireball Festival

Abstract: This study aims to investigate problems with local community participation in the Naga

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Accordingly, special events comprised of various short-term activities, which play a role as a pull factor to attract tourists’ visit. In addition to that, it was found that both festivals and events are the key determinants or motivators for tourists in making choice of visit to one particular tourism destination (McKercher et al., 2006; Maneenetr and Tran, 2014). A study by Kamarul and Dahnil (2012) has revealed that events and festivals are the crucial elements that attract both local and international tourists to visit Malaysia, and this also applies to other tourism destinations (Wilson et al., 2016).…”
Section: Literature Review and Theoretical Foundationmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, special events comprised of various short-term activities, which play a role as a pull factor to attract tourists’ visit. In addition to that, it was found that both festivals and events are the key determinants or motivators for tourists in making choice of visit to one particular tourism destination (McKercher et al., 2006; Maneenetr and Tran, 2014). A study by Kamarul and Dahnil (2012) has revealed that events and festivals are the crucial elements that attract both local and international tourists to visit Malaysia, and this also applies to other tourism destinations (Wilson et al., 2016).…”
Section: Literature Review and Theoretical Foundationmentioning
confidence: 99%
“…Past studies have propounded that tourists tend to make their choice of tourism destination by relying on the range of tourism activities available at a destination (Koutra, 2005; Maneenetr and Tran, 2014). Thus, the support from local community, such as by providing better services and range of tourism activities, those are important in ensuring high quality in every tourism services (Tosun et al., 2007) that facilitate the desired level of relaxation for tourists.…”
Section: Literature Review and Theoretical Foundationmentioning
confidence: 99%
“…The qualitative approach is, on the contrary, very rarely used, and involves individual interviews, focus group interviews and participant observation (Gupta, Prakash, 2014;Maneenetr, Tran, 2014).…”
Section: Introductionmentioning
confidence: 99%